1997
DOI: 10.1016/s0006-3495(97)78655-7
|View full text |Cite
|
Sign up to set email alerts
|

K+ channel inactivation mediated by the concerted action of the cytoplasmic N- and C-terminal domains

Abstract: We have examined the molecular mechanism of rapid inactivation gating in a mouse Shal K+ channel (mKv4.1). The results showed that inactivation of these channels follows a complex time course that is well approximated by the sum of three exponential terms. Truncation of an amphipathic region at the N-terminus (residues 2-71) abolished the rapid phase of inactivation (r = 16 ms) and altered voltage-dependent gating. Surprisingly, these effects could be mimicked by deletions affecting the hydrophilic C-terminus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
168
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(180 citation statements)
references
References 32 publications
(37 reference statements)
11
168
1
Order By: Relevance
“…It has also been shown that the association of KChIPs at the N terminus of Kv4 channels impairs open-state inactivation (41). Electrophysiological studies support the idea that both the N and C termini of Kv4 channels interact to regulate the inactivation kinetics (40,42), opening the possibility that such interactions are modulated by binding of KChIPs at the N terminus (34,38). It is also proposed that the N terminus functions as a membrane transport control, which in the absence of KChIPs anchors Kv4 channels near the perinuclear region of the cell (43,44).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been shown that the association of KChIPs at the N terminus of Kv4 channels impairs open-state inactivation (41). Electrophysiological studies support the idea that both the N and C termini of Kv4 channels interact to regulate the inactivation kinetics (40,42), opening the possibility that such interactions are modulated by binding of KChIPs at the N terminus (34,38). It is also proposed that the N terminus functions as a membrane transport control, which in the absence of KChIPs anchors Kv4 channels near the perinuclear region of the cell (43,44).…”
Section: Discussionmentioning
confidence: 97%
“…Kv4 channel inactivation has been dissected in numerous biophysical studies into three separate processes: open state, closed state, and slow inactivation (15,20,21). Open state inactivation utilizes a pore block produced by the Kv4 cytoplasmic N terminus and is lost by deletion of the Kv4 N terminus or binding of KChIP proteins to the N terminus (16,22).…”
Section: Kchip3 Rescues Function Of Znmentioning
confidence: 99%
“…The N terminus of Kv4.2 is clearly involved in inactivation gating, since deletion of this region produces slowed inactivation. Moreover, experiments on the functional properties of the N terminus show that it can act as a pore-binding peptide (15)(16)(17). Therefore, the gating changes produced by KChIPs might depend on the binding and sequestering of the Kv4 N terminus, causing an alteration to a complex set of allosteric interactions that involve other structural elements of the channel (18).…”
mentioning
confidence: 99%
“…It is known that in Shaker-like K ϩ channels, C termini are involved in a variety of processes that range from channel gating (10,11) and voltage sensitivity (4) to the binding of the membrane-associated guanylate kinases (12). They also participate in channel assembly in Kv 2.1 (13,14).…”
mentioning
confidence: 99%